DIAGNOSTICS OF LEVELS OF FUTURE PRIMARY SCHOOL TEACHERS’ INFORMATIVE COMPETENCE (Journal of Information Technologies in Education (ITE), 2013)
The article describes the main structural components of future primary school teachers’ informative competence according to modern researches, diagnostic methods and results of future primary school teachers’ informative competence levels are analyzed
Keywords: informative competence; motivational-evaluative; cognitive-operational; regulative-reflective components; trial; basic; reproductive-search levels